2014
DOI: 10.4103/1755-6783.144997
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of glaucoma among primary care givers in a developing country

Abstract: Background: Glaucoma is the leading cause of untreatable blindness throughout the world, and it is commoner in the black race; therefore, primary health care givers should have some knowledge of glaucoma. The aim of this study is to determine the knowledge of primary health care givers about glaucoma in Sagamu Local Government area of Ogun State. Materials and Methods: A cross-sectional descriptive study of primary care givers in Sagamu, Ogun Sate was carried out between March and May 2010. A structured, self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
2
8
3
Order By: Relevance
“…One explanation for this may be that several of these studies focused on rural populations, with the exception of one other urban study in Togo reporting 30% awareness (12) . Conversely, the proportion is lower than findings among West African health science students, health workers and eye clinic attendees (14,15,17,18) , whose awareness ranged from 69 -100%. This is not surprising given the inherent bias of these populations.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…One explanation for this may be that several of these studies focused on rural populations, with the exception of one other urban study in Togo reporting 30% awareness (12) . Conversely, the proportion is lower than findings among West African health science students, health workers and eye clinic attendees (14,15,17,18) , whose awareness ranged from 69 -100%. This is not surprising given the inherent bias of these populations.…”
Section: Discussioncontrasting
confidence: 56%
“…Other studies among West African students, health workers and eye clinic attendees have found higher numbers having heard of glaucoma but few with actual knowledge about the disease (14)(15)(16)(17)(18) . Consequently, West Africa has a large unmet need for glaucoma health promotion (9,10,12,16,19) .…”
Section: Introductionmentioning
confidence: 98%
“…counted for by the high level of development, high literacy rate and good access to health care in developed countries like Canada. Also, this study result predictably differs from that of a study conducted among Primary care givers, whose training gave them the opportunity to know about glaucoma, in Shagamu, Ogun State, with awareness of 97%[22]. The low level of awareness could be because of the insidious and initial asymptomatic nature of the disease and Open Journal of Ophthalmology poor access of the people to eye clinics with glaucoma screening facility and treatment.…”
contrasting
confidence: 77%
“…According to risk factors of glaucoma Debjit et al 2012, Onabolu 2014 reported that: The major risk factors for glaucoma include the following: High intraocular pressure, age 50 or older, family history of glaucoma, African Americans, suspicious optic nerve appearance (cupping > 50%), thin cornea, high myopia, diabetes, hypertension, eye injury or surgery, history of steroid use, migraine, headaches, sleep apnea. Smoking is the leading cause of preventable death worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge was defined as having some correct understanding of the disease (Onabolu, 2014). Risk factors: describes features that may be causal in disease, as they are statistically associated with the disease, and were (or could have been) present before its occurrence, and could conceivably have played an essential role along with other factors in incident disease.…”
Section: Operational Definitionsmentioning
confidence: 99%